PROTOTYPE ALAT PENGERING TRAY DRYER DITINJAU DARI PENGARUH TEMPERATUR DAN WAKTU TERHADAP PROSES PENGERINGAN MIE KERING - Purnamasari, Indah (Politeknik Negeri Sriwijaya, 2019)
According to the Standard of National Industry No 01-7890-2010, the dried noodle is the noodle that has been produced with drying process till its moisture content is 8-10% left. The unit production system of instant noodle through the drying process is operated with frying process at vacuum condition. This drying process uses amounts of energy and high air temperature. This process is enough strategic to design, research, and innovate subsequently it is able to build the tray dryer instrument. The drying time needed (1-2 hours) is depending on dimension of the unit, the material capacity as the feed dehumidified, and the heat source that come from steam boiler/coil of air heater. The fabrication of this unit is supposed to make instant noodle/dried noodle based on SNI standard. The product obtained will be analyzed to determine the moisture content remained inside dried noodle and also to find out the operational condition of tray dryer unit. The most optimum drying time is 120 minutes at the drying temperature of 70ᵒC with the moisture content remained as much as 9.3% inside dried noodle and it’s filled up the SNI standard namely 8-10% and the process efficiency of this unit is 61.99%.